Dimensions of tax burden: a review on OECD countries - Celikay, Ferdi (2020)
Purpose: The tax burden, defined as the ratio of the collected taxes in a particular period against the total product, is commonly used to determine the effect of fiscal and tax policies on the socioeconomic structure. The purpose of this study is to examine how the changes in some macroeconomic indicators affect the tax burden. Design/methodology/approach: System generalized method of moments approach is used for 34 Organisation for Economic Co-operation and Development (OECD) members in the period of 1993-2016. Findings: Based on the research findings, variables such as income per capita, foreign trading volume, the capacity of employment, unemployment and economic share of industry sector effect tax burden in a statistically significant and positive direction. The reason that lies behind the positive effect of unemployment on tax burden is the fact that the sense of social state is not abandoned. Thus, it is predicted that the state will increase public transfer expenditures in the short term due to unemployment, this increase will impose a financial burden on the public sector both in the medium and long term and finally, there will be an increase in the tax burden. Originality/value: Results in the literature suggest that there are many reasons for increasing tax burden such as socio-economic development, financial and organizational structure and the globalization process. However, according to this study, it seems that gross domestic product per capita, the size of the industry sector, openness, employment capacity and unemployment rate also have a positive and significant effect on tax burden in the long run. Ultimately, these results demonstrate that tax burden, one of the most important indicators of the public sector size in the sample of the states and period in hand, is influenced positively by all independent variables and increases slightly but surely. These results suggest that the tax state is still a determinative factor in the socioeconomic field within its taxation tools. Doi: https://doi.org/10.1108/JEFAS-12-2018-0138